1996
DOI: 10.3109/01902149609046042
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Clearance in Large and Small Airways in Chronic Bronchitis

Abstract: Tracheobronchial clearance was studied twice in 16 patients with chronic obstructive bronchitis after inhalation of 6 microns (aerodynamic diameter) monodisperse Teflon particles labeled with 111In. At one exposure the particles were inhaled at an extremely slow flow, 0.05 L/s; at the other they were inhaled at a normal flow, 0.5 L/s. Theoretical calculations and experimental data in healthy subjects indicate particle deposition mainly in the smallest ciliated airways using 0.05 L/s, i.e., in the bronchiolar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…In an earlier study, a relationship was found between FEV1 values and clearance for subjects with chronic bronchitis [23]. Subjects with cystic fibrosis and FEV1 ,70% were found to have worse long-term clearance compared with those with FEV1 .70% [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier study, a relationship was found between FEV1 values and clearance for subjects with chronic bronchitis [23]. Subjects with cystic fibrosis and FEV1 ,70% were found to have worse long-term clearance compared with those with FEV1 .70% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after inhalation, and 24 h later, radioactivity was measured using two 127651-mm NaI detectors fitted with collimators [21][22][23][24][25][26]. The c-spectra from each detector were acquired separately.…”
Section: Measurement Of Radioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size calculation based on variability data from the pooled SD in a previous study comparing clearance between healthy subjects and patients with chronic bronchitis [19], showed a demand of 12 individuals in each group to detect a difference of one SD with a power of 80%. The authors were finally able to recruit 11 CF patients.…”
Section: Methodsmentioning
confidence: 99%
“…By inhaling rather large aerosol particles (6 µm) extremely slowly (0.05 liter/s), deposition by sedimentation takes place mainly in the small ciliated airways due to the prolonged transit time. Since deposition in these airways is practically independent of airway resistance, clearance data can be compared in healthy subjects [6]and patients with airway obstruction [9, 10, 11]. In a recent study, we found that particles clear equally well from the bronchiolar region in a group of healthy subjects and asthmatics on regular treatment with anti-inflammatory drugs, i.e.…”
Section: Introductionmentioning
confidence: 99%